2018
DOI: 10.1002/jac5.1061
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a hemophilia management program improves clinical outcomes

Abstract: Introduction Hemophilia is a rare, inherited, coagulation disorder that impairs the body's ability to cease bleeding, making hemophiliacs susceptible to bleeding episodes. These patients often require multiple doses of clotting factor concentrates to help maintain hemostasis. In fiscal year (FY) 2016, Rush University Medical Center's drug expense for clotting factor concentrates totaled $4.6 million, which accounted for approximately 15% of the total drug budget. The Department of Pharmacy developed a Hemophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Several publications have highlighted the impact of Hemostatic and Antithrombotic Stewardship Programs (Table 1). 9‐18 Of the 10 stewardship programs with reported outcomes, four programs had initiatives only focused on anticoagulation stewardship, four programs only focused on hemostatic stewardship, and two programs had a combination of select interventions involving anticoagulation and hemostatic stewardship. Reported anticoagulation interventions primarily involve anticoagulant prescribing and institutional protocol adherence, as well as focused efforts on heparin‐induced thrombocytopenia (HIT) management to reduce intravenous direct thrombin inhibitor (IV DTI) use 9‐12,17,18 .…”
Section: Existing Hemostatic And/or Antithrombotic Stewardship Progra...mentioning
confidence: 99%
See 3 more Smart Citations
“…Several publications have highlighted the impact of Hemostatic and Antithrombotic Stewardship Programs (Table 1). 9‐18 Of the 10 stewardship programs with reported outcomes, four programs had initiatives only focused on anticoagulation stewardship, four programs only focused on hemostatic stewardship, and two programs had a combination of select interventions involving anticoagulation and hemostatic stewardship. Reported anticoagulation interventions primarily involve anticoagulant prescribing and institutional protocol adherence, as well as focused efforts on heparin‐induced thrombocytopenia (HIT) management to reduce intravenous direct thrombin inhibitor (IV DTI) use 9‐12,17,18 .…”
Section: Existing Hemostatic And/or Antithrombotic Stewardship Progra...mentioning
confidence: 99%
“…Reported anticoagulation interventions primarily involve anticoagulant prescribing and institutional protocol adherence, as well as focused efforts on heparin‐induced thrombocytopenia (HIT) management to reduce intravenous direct thrombin inhibitor (IV DTI) use 9‐12,17,18 . Other programs aimed at the optimization of CFC use have reported optimization of patient selection for prothrombin complex concentrate (PCC) administration for anticoagulation reversal, preferential use of activated prothrombin complex concentrate (aPCC) over recombinant factor VIIa (rFVIIa) for hemophilia patients with inhibitors, CFC formulary management, implementation of 340B Drug Pricing Program for CFCs, and continuous infusion CFC administration 13‐16 . Notably, across all programs, pharmacists have been essential to program development and in most cases are heavily involved in direct patient care for patients receiving anticoagulants and CFCs.…”
Section: Existing Hemostatic And/or Antithrombotic Stewardship Progra...mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, two US studies have shown that involvement of a pharmacist in the management of recombinant and plasma derived factor therapies for hemophilia improves patient management and reduces associated costs. 8,9 As in Canada, in the US pharmacists are not typically part of the comprehensive care team for the hemophilia population. The Hemophilia Management Program 8 and The Factor Stewardship Program 9 were conducted to evaluate the impact of including a pharmacist in the management of hemophilia patients.…”
Section: Introductionmentioning
confidence: 99%